BUSINESS FEASIBILITY STUDY OF CU.MIE RESTAURANT IN NORTHERN JAKARTA REGION - Nagan, Neddie; Wowor, Wulannmeiaya (IJOSMAS, 2022)
This study looks into the feasibility of Cu.mie restaurant as a business in the region of Northern Jakarta. Cu.mie Restaurant main product is Squid Ink Noodle with various topping with the taste of Indonesia flavors. This study is driven by the continual growth of food and beverages industry and the recovering economy post COVID-19. Data is gathered using online questionnaire filled out by 119 respondents. Further, secondary data is utilized to further support analysis; gathered through external sources. Several aspects of business management such as financial, human resources, operational, and marketing are considered as measures of the feasibility of Cu.mie restaurant. This study finds that Cu.mie restaurant is feasible to operate and profitable with estimated break-even point of 3 years, 8 months, and 11 days. Keywords — Business Feasibility Study, Restaurant, Noodle, Northern Jakarta.